GENDERED CULTURES: ECONOMI CAPITAL DALAM BUDAYA SIRI’ PERNIKAHAN MASYARAKAT BUGIS DI TANAH MELAYU - Mulya, Misda; Subaidi, Subaidi (Universitas Cokroaminoto Yogyakarta, 2023)
The Bugis character trait of siri' napecce siri' is the ability to empathise with the pain or suffering of others within the community. An example of this trait is seen in the Bugis marriage culture, which is not only practiced in Makassar or among Bugis communities in South Sulawesi (its place of origin), but also among almost all Bugis communities throughout the islands. This study focuses on the Bugis community residing along the East Coast of Tanjung Jabung Timur Regency in Jambi Province and the coastal areas of Indragiri Hilir Regency in Riau Province, both located on the island of Sumatra in Indonesia. The study examines the continued practice of the Uang Panai tradition in Bugis wedding ceremonies in the coastal region that connects the two provinces. The research method used was qualitative, employing observation and interviews, as well as secondary data through literature review. In terms of the origin of uang panai', it differs greatly from its initial form as a form of appreciation for women, transforming into a spending currency that has turned it into a capitalist economic concept wrapped in the siri' culture. The results lead to gender inequality, where Bugis women must increase their value to be considered worthy of a high bride price. Additionally, Men must prepare themselves to become actors who will be pressured to be economically capable, as the amount of dowry determined by the woman's family is an absolute requirement that must be fulfilled in Bugis society's marriage tradition to preserve the culture of Siri' (shame).